Interview with Sadhan Gupta CPI(M) leader, former MP and Attorney-General on Marxist Student movement in 1940's and Trade Union movement, interviewed by Kabir in Kolkata - Kabir, Shahriar.
Interview with Sadhan Gupta CPI(M) leader, former MP and Attorney-General on Marxist Student movement in 1940's and Trade Union movement, interviewed by Kabir in Kolkata.